35 terms

9÷9∧⁻4/5

9∧9/5

x∧1/4 × x1/3

X ∧7/12

2/x∧-1/4

2x∧1/4

(x∧15)/y∧6

x∧5/y∧2

7 3square root 125

125= 5×25=5×5 = 5×7 =35

Simplify 5∧3/2 × 5∧1/2

5∧4/2 = 5²

= 25

= 25

Simplify 2/X∧⁻¼

2x∧¼

Simplify (2∧1/3 × 5∧1/6)⁶

2² × 5¹ = 4 × 5

= 20

= 20

Simplify (X¹⁵/Y⁶)∧1/3

X⁵/Y²

Simplify −³√10 × −4³√100

4³√10 ×100 = 4³√10 × 10 × 10

4 × 10 = 40

4 × 10 = 40

use the product to a power rule to solve

(ab)²

(ab)²

a²b²

simplify 11∧¼÷11∧¾

11∧½

combine these radicals

2²√3 + 2²√3

2²√3 + 2²√3

4²√3

use the quotient rule to solve

a∧m÷ aⁿ

a∧m÷ aⁿ

a∧m−n

what is the multiplication rule?

a∧m+a∧n = a∧mn

Simplify

5∧3/2 × 5∧1/2

5∧3/2 × 5∧1/2

5∧4/2 = 5∧2

=25

=25

Simplify

2x∧1/2 × 4x^3/4

2x∧1/2 × 4x^3/4

=8x^5/4

Simplify

x^1/4 × x^1/3

x^1/4 × x^1/3

=x^7/12

Simplify

(64y^8)^1/2

(64y^8)^1/2

64^1/2y^4

=8y^4

=8y^4

Simplify

5x^2/3 + (x^5/4)^8/15

5x^2/3 + (x^5/4)^8/15

5x^2/3 + x^2/3

=6x^2/3

=6x^2/3

-3(^4√4) -2(^4√64)

-7(^4√4)

(3^3/7^3)^-1\3

7\3

^3√-216n^4

6n(^3√n)

-7^3√108x^7 y^5

-21x^4 y^2 ^3√4

9\9^-4/5

9^9\5

simplify 5^3/2 x 5^1/2

5^4/2= 5²

=25

=25

simplify 7 ³√125

7³√25x5

7 ³√5x5x5

7x5

=35

7 ³√5x5x5

7x5

=35

simplify 2/x^-1/4

2x¼

simplify (64y^8)½

6y½ y^4

=8y^4

=8y^4

simplify 2x½ x 4x¾

8x^5/4

adv exp.

adv exp.

simplest form of radicals:

no perfect nth powers as factors and any denominator has been rationalized.

a^m * a^n =

a∧m+n

a^-m =

1 / a^m

ax^m ± bx^m =

(a + b)x^m

a^m / a^n

a^m-n